2021
DOI: 10.1155/2021/6642600
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology-Based Approach to Comparatively Predict the Active Ingredients and Molecular Targets of Compound Xueshuantong Capsule and Hexuemingmu Tablet in the Treatment of Proliferative Diabetic Retinopathy

Abstract: Background. Compound Xueshuantong capsule (CXC) and Hexuemingmu tablet (HXMMT) are two important Chinese patent medicines (CPMs) frequently used to treat proliferative diabetic retinopathy (PDR), especially when complicated with vitreous hemorrhage (VH). However, a network pharmacology approach to understand the therapeutic mechanisms of these two CPMs in PDR has not been applied. Objective. To identify differences in the active ingredients between CXC and HXMMT and to comparatively predict and further analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…This pathway was previously evidenced as functionally significant in neurotransmitter-mediated disorders such as alcohol dependence disorder (42), autism spectrum disorders (43), Parkinson's disease (44), and some types of lung cancer (45). Besides, the pathway was found to be enriched in proliferative diabetic retinopathy and age-related macular degeneration (46,47). This pathway regulates multiple neuroreceptors and their associated distant signaling molecules, such as 5hydroxytryptamine (5-HT, serotonin) and GABA.…”
Section: Discussionmentioning
confidence: 96%
“…This pathway was previously evidenced as functionally significant in neurotransmitter-mediated disorders such as alcohol dependence disorder (42), autism spectrum disorders (43), Parkinson's disease (44), and some types of lung cancer (45). Besides, the pathway was found to be enriched in proliferative diabetic retinopathy and age-related macular degeneration (46,47). This pathway regulates multiple neuroreceptors and their associated distant signaling molecules, such as 5hydroxytryptamine (5-HT, serotonin) and GABA.…”
Section: Discussionmentioning
confidence: 96%
“…HXMMT is composed of 18 herbs. Modern pharmacological studies have shown that HXMMT can effectively inhibit platelet aggregation and adhesion and improve blood rheology ( 70 , 71 ). In addition, several clinical studies have shown that HXMMT can effectively improve fundus hemorrhage and exudation, and stabilize lesion efficacy in patients with NPDR ( 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors also noted that there are some reports on the efficacy of XST capsules in the treatment of PDR, which can reduce edema and eliminate vitreous hemorrhage. 93 , 94 The network pharmacology analysis showed that the mechanism of XST for PDR was mainly related to regulation of oxidative stress as well as regulation of blood vessels and blood coagulation. 93 …”
Section: Discussionmentioning
confidence: 99%
“… 93 , 94 The network pharmacology analysis showed that the mechanism of XST for PDR was mainly related to regulation of oxidative stress as well as regulation of blood vessels and blood coagulation. 93 …”
Section: Discussionmentioning
confidence: 99%